2019
DOI: 10.14393/bj-v35n1a2019-41710
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial activity of Cinnamomum zeylanicum essential oil and trans-Cinnamaldehyde against resistant Mycobacterium tuberculosis

Abstract: The essential oil (EO) extracted from the bark of Cinnamomum zeylanicum (Czey; also known as cinnamon), mostly derives its properties from its major compound trans-cinnamaldehyde (TCin). The present study evaluated the antimycobacterial activity of the essential oil from Czey (CzeyEO) and TCin against sensitive and resistant clinical isolates of Mycobacterium tuberculosis, as well as the combinatorial effects of CzeyEO and TCin with the anti-tuberculosis (TB) drugs rifampicin (RIF) and isoniazid (INH). The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Hence, it is favorable to have extracts with high concentrations of Cinnamic acid for better diabetic control. Cinnamaldehyde is identified as the major compound present in Cinnamon extracted using hydro distillation in several studies (Kaskoos, 2019;Mota, Campelo & Frota, 2019). The α-amylase inhibition evaluated using a combination of (E)-Cinnamaldehyde and (E)-Cinnamyl acetate has shown better potency than Cinnamaldehyde alone (Sihoglu Tepe & Ozaslan, 2020).…”
Section: /18mentioning
confidence: 99%
“…Hence, it is favorable to have extracts with high concentrations of Cinnamic acid for better diabetic control. Cinnamaldehyde is identified as the major compound present in Cinnamon extracted using hydro distillation in several studies (Kaskoos, 2019;Mota, Campelo & Frota, 2019). The α-amylase inhibition evaluated using a combination of (E)-Cinnamaldehyde and (E)-Cinnamyl acetate has shown better potency than Cinnamaldehyde alone (Sihoglu Tepe & Ozaslan, 2020).…”
Section: /18mentioning
confidence: 99%
“…2015; Mota et al . 2019). Even there are reports suggested that trans‐cinnamide at its sub‐MIC (1 µg ml −1 ) has a synergistic effect with first‐line TB antibiotics, mainly isoniazid, and RIF by inhibiting the synthesis of mycolic acid and proteins (Rastogi et al .…”
Section: Ethnomedicinal Plants Of India and Their Key Bioactive Molecules On Tb Managementmentioning
confidence: 99%
“…The chemical composition in the aqueous extracts in our study, slightly deviated from Hafizur et al, (2015) Manuscript to be reviewed acid for better diabetic control. Cinnamaldehyde is identified as the major compound present in Cinnamon extracted using hydro distillation in several studies (Paranagama et al, 2001;Kaskoos, 2019;Mota, Campelo & Frota, 2019). The α-amylase inhibition evaluated using a combination of (E)-Cinnamaldehyde and (E)-Cinnamyl acetate has shown better potency than Cinnamaldehyde alone (Sihoglu Tepe & Ozaslan, 2020).…”
Section: Gc-ms Technique Is a Powerful And Suitable Tool For The Detementioning
confidence: 99%